PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA POP-UP BOOK PADA MATERI BANGUN DATAR DI SMP - Lusianty Bakara; Andinasari Andinasari; Nike Astiswijaya (Program Studi PGSD Universitas Flores, 2023)
Education plays a vital role in the progress of a nation as it involves the imparting of attitudes, ethics, knowledge, and skills between educators and students. Mathematics holds great importance for the advancement of science and technology. This study aims to develop a pop-up book as an alternative learning medium to enhance students' understanding of mathematics, particularly in the topics of triangles and quadrilaterals. Pop-up books capture students' attention through visually engaging and interactive elements that surprise and awe when opened. The research adopts the development research method, comprising two stages: the preliminary stage and the formative evaluation stage. The study was conducted at SMP N 3 Air Kumbang, involving 28 seventh-grade students as research subjects. The findings indicate that the use of pop-up books in mathematics education received positive appreciation from students. The media assists students in comprehending plane geometry concepts and enhances their learning motivation. Additionally, the utilization of pop-up books yields positive effects on students' learning outcomes. Thus, this research produces a valid and practical learning medium in the form of a pop-up book for triangles and quadrilaterals. The implementation of this media is expected to enhance students' understanding and motivation in learning mathematics at the junior high school level.